2022
DOI: 10.3390/nu14235144
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Intake and Biomarkers of Iron Status in Slovenian Population: Results of SI.Menu/Nutrihealth Study

Abstract: Inadequate iron intake and iron deficiency are recognised as a public health problem in the population at large, and particularly in specific subpopulations. Dietary iron intake was analysed using data of the national Slovenian food consumption study, SI.Menu (n = 1248 subjects; 10–74 years), while iron status was evaluated with laboratory analyses of blood haemoglobin, serum ferritin, and iron concentration in samples, collected in the Nutrihealth study (n = 280, adults). The estimated daily usual population-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…The urea levels found in the population are high and correlated with the declared frequency of rice and white fish consumption, so it would be advisable to study this fact in depth and make dietary adaptations that would benefit better urea values [24] by controlling the amounts of food to be avoided in uremia. Magnesium seems to benefit from the frequency of consumption of dairy products in this population [25], as does ferritin with meat consumption and hematocrit with consumption of legumes [26], all of which are very important for optimum performance and therefore foods that would favour the health and sporting improvements of these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The urea levels found in the population are high and correlated with the declared frequency of rice and white fish consumption, so it would be advisable to study this fact in depth and make dietary adaptations that would benefit better urea values [24] by controlling the amounts of food to be avoided in uremia. Magnesium seems to benefit from the frequency of consumption of dairy products in this population [25], as does ferritin with meat consumption and hematocrit with consumption of legumes [26], all of which are very important for optimum performance and therefore foods that would favour the health and sporting improvements of these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Haem iron is absorbed from the gastrointestinal tract with notably higher efficiency ( 29 ). Notably, the consumption of haem iron, rather than total iron intake, exhibits a significant correlation with ferritin levels ( 16 , 17 ). Extensive research has demonstrated the enhanced effectiveness of a combination of folic acid and iron, as opposed to iron supplementation alone, in addressing ID ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In certain research studies, a notable and statistically significant positive association between ferritin levels and iron intake was evident (16,17). Inadequate iron consumption emerged as a noteworthy predictor for maintaining serum ferritin levels below 30 ng/ml, though not for achieving ferritin concentrations <100 ng/ml (16). The accuracy of these findings necessitates validation within a more expansive and diverse population sample.…”
Section: Introductionmentioning
confidence: 97%
“…The intake of these nutrients was deficient in adolescents of both sexes at a 100% rate for vitamin D, 91% for fibre, 88% for folate, 44% for iron, and 38% for vitamin B12. Among girls, the deficiency in iron and vitamin B12 was even more pronounced, at 73% and 44%, respectively [85][86][87][88]. Another study focusing on adolescents aged 14-16 years in Slovenia also highlighted worrisome nutritional trends.…”
Section: Prevalence Of Unhealthy Lifestyles and Other Major Riskmentioning
confidence: 98%